Outcome of 3 year surveillance colonoscopy in patients with intermediate risk adenomas: analysis of the NHS Bowel Cancer Screening Programme National Database. (13th March 2011) - Majumdar, D; Lee, T J; Nickerson, C; Patnick, J; Rutter, M D
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) commenced in England in August 2006. Patients are offered colonoscopy if they have a positive FOB test. If a patient is found to have 3 to 4 small (<10 mm) adenomas or 1 to 2 adenomas of which at least one is 10 mm or greater in size, they are defined as being at 'intermediate risk' of having advanced adenomas or cancer in the future.1 Such patients are offered a surveillance colonoscopy three years after their screening colonoscopy.2 Methods: The aim of the study was to assess the findings at, and hence appropriateness of 3-year surveillance colonoscopy for intermediate risk patients. Data regarding each patient entering the screening programme is contemporaneously recorded on the National BCSP database. The database was interrogated for individuals who underwent screening colonoscopy between August 2006 and September 2007 and who were classified as intermediate risk. Details of the endoscopic and histological findings at 3-year surveillance colonoscopy were ascertained. Findings at surveillance colonoscopy were classified according to the BSG Adenoma surveillance guidelines. Patients with incomplete datasets were excluded. Results: 352 patients underwent 3-year surveillance colonoscopy. This accounts for 10.3% of all patients undergoing screening colonoscopy in that time period. The mean age of patients was 67.1 years. 243/352 (69.0%) were male. At 3-year surveillance, 13 patients (3.7%) were categorized as high risk, 42 (11.9%) intermediate risk, 86 (24.4%) low risk and 202 (57.3%) had normal colonoscopies (i.e., no adenomas detected). No cancers were detected. 9 (2.6%) had incomplete data. Conclusion: Approximately 40% of intermediate risk patients had one or more adenomas detected. A small proportion of individuals undergoing 3-year surveillance colonoscopy have multiple or large adenomas. In this group, no surveillance cancers were detected. Although the number of individuals in this study is relatively small, these data suggest that the 3-year interval for surveillance may be unnecessary for many intermediate risk individuals. Further work on larger datasets may help identify individuals at high risk of having advanced adenoma at surveillance. This may allow the criteria for determining surveillance interval to be refined.